How satisfied UPV students are with sanitation, water services and campus security? - Gil, shirley; Legaste, Jesrel Faith; Margen, Lyra May.; Perez, Barbara; Yap, Abigail Louie (2003)
The main purpose of the research is to determine the level of satisfaction of the students of UPV on the services rendered by the offices of sanitation, water services, and campus securty. The types of data that the researchers used are the primary data and secondary data. In the primary data, the researcher used the information they got from the respondents like the result given to them and the interviews conducted to the personnel concerned with sanitation, water services, and campus security. Secondary data consist of data provided by these offices like the information about their respective cancers and their organization. The type of data collection that the researcher used in gathering data are the in-office interview where the researchers will conduct interviews to the department heads or personnel of each office and the drop-off interviews on which they will have questionnaires to the respondent they have chosen for them to answer. The researcher conducted an interview and survey last August 22-October 7 from the persons in-charge of sanitation, water services and campus security and the students who are our respondents both from Iloilo City and Miag-ao campuses. The researchers used a conventional approach in determining their sample size. The researchers used 100 respondents where 40 respondents from CM, 4 from SOTECH, 10 came from CFOS and 46 from CAS. In analyzing the data, the researchers used the two types of statistical analysis which are the descriptive and inferential analysis. The measures that the researcher used in the descriptive analysis are the mean,percentage and frequency distribution, They are used to determine average score of the respondents in each category of the questionnaire. In inferential analysis the researchers sedd the nonparametric measure of Kruskal-Wallis H-Test to test whether or not there is a significant difference between variables with three or more categories.
Research Paper (BA 174 - Marketing Research). -- Iloilo City : UPV-CM, October 20, 2003.